Binding and Unwinding the British Empire: Philadelphia's German Merchants as Consumer and Political Revolutionaries. - ZONDERMAN, ANDREW (Early American Studies, An Interdisciplinary Journal)
This article explores the German-speaking merchant community that arose in mid-eighteenth-century Philadelphia, and its members' efforts to integrate themselves and fellow Central European immigrants into British systems of commerce, credit, law, and politics. These naturalized merchants developed commercial ties around the Atlantic--in Great Britain, Iberia, and the Caribbean--and worked to align their largely colinguistic customer bases with British tastes and goods. They also sought to assist new arrivals through their civic and political engagement, especially through the newly formed German Society of Pennsylvania. After decades of striving to integrate themselves into the British Empire, Philadelphia's German merchants emerged as vocal critics of Parliament's imperial reforms in the late 1760s. They feared that the new laws subverted their economic gains and equality as naturalized subjects. By the 1770s German merchants financed the Patriot war effort and served within the newly independent Pennsylvania government. The merchants' activities reveal how Central Europeans, despite originating beyond Europe's metropoles, became transformative figures in the eighteenth-century Atlantic economy as well as in Great Britain's empire and its fracturing in North America.